Uncovering Interfacial Oxygen‐Bridged Binuclear Metal Centers of Heterogenized Molecular Catalyst for Water Electrolysis - Yu, Zhou; Li, Jian‐Ping; Xu, Xian‐Kun; Ding, Zhong‐Chen; Peng, Xiao‐Hui; Gao, Yi‐Jing; Wan, Qiang; Zheng, Ju‐Fang; Zhou, Xiao‐Shun; Wang, Ya‐Hao (Advanced science, 2025)
The success of different heterogeneous strategies of organometallic catalysts has been demonstrated to achieve high selectivity and activity in photo/electrocatalysis. However, yielding their catalytic mechanisms at complex molecule‐electrode and electrochemical interfaces remains a great challenge. Herein, shell‐isolated nanoparticle‐enhanced Raman spectroscopy is employed to elucidate the dynamic process, interfacial structure, and intermediates of copper hydroxide‐2‐2′ bipyridine on Au electrode ((bpy)Cu(OH)2/Au) during the oxygen evolution reaction (OER). Direct Raman molecular evidences reveal that the interfacial (bpy)Cu(OH)2 oxidizes into Cu(III) and bridges to Au atoms via oxygenated species, forming (bpy)Cu(III)O2‐Au with oxygen‐bridged binuclear metal centers of Cu(III)‐O‐Au for the OER. As the potential further increases, Cu(III)‐O‐Au combines with surface hydroxyl groups (*OH) to form the important intermediate of Cu(III)‐OOH‐Au, which then turns into Cu(III)‐OO‐Au to release O2. Furthermore, in situ electrochemical impedance spectroscopy proves that the Cu(III)‐O‐Au has lower resistance and faster mass transport of hydroxy to enhance OER. Theoretical calculations reveal that the formation of Cu(III)‐O‐Au significantly modify the elementary reaction steps of the OER, resulting in a lower potential‐determining step of ≈0.58 V than that of bare Au. This work provides new insights into the OER mechanism of immobilized‐molecule catalysts for the development and application of renewable energy conversion devices. In situ Raman monitoring of an electrochemically induced interfacial oxygen‐bridged Cu(III)‐O‐Au binuclear center in heterogenized molecular catalysts, could combine surface hydroxyl groups to form the important intermediate of Cu(III)‐OOH‐Au, which then turns into Cu(III)‐OO‐Au to release O2. This significantly modifies the elementary reaction steps and lowers the overpotential for oxygen evolution reaction.